The multisensory film experience : a cognitive model of experiential film aesthetics - Antunes, Luis Rocha (Intellect, 2016)
When the lights dim in a movie theater and the projector begins to click and whir, the light and sounds of the motion picture become the gateway to a multisensory experience. Moving beyond the oft-discussed perceptual elements of vision and hearing, "The multisensory film experience" analyzes temperature, pain, and balance in order to argue that it is the "experience" of film that is inherently multisensory, not the medium. Luis Rocha Antunes here explores the work of filmmakers Erik Jensen, Gus Van Sant, and Ki-Duk Kim to offer new insights into how viewers experience films and understand their stories.